The woman who killed Marvin Hammel [large type] - Crigger, C. K. (Crigger, C. K. Woman who, 2023)
"Shay Billings and January Schutt have been married four months when he's summoned by the local bank president to a meeting. With the final payment due on his land, Shay rides to town for the meeting, then is murdered on the way home . . . The bank president declares the loan in arrears and informs January the bank is taking everything except the clothes on her back. Devastated by Shay's death, January knows skullduggery is afoot and vows to fight back. Worse, it seems she'll have to go after Shay's murderer herself as the local sheriff lacks the backbone. Everything ties together, to her mind. The foreclosure nothing more than downright theft, the murder an act of revenge by the widow of Shay's old enemy. But January has friends, too, especially in Ford Tervo, a deputy U.S. marshal who had been Shay's friend. Now, vowing her own revenge, the final showdown becomes two widows duking it out."--